Philodina gregaria Murray 1910 - LUKASHANETS, Dzmitry A.; VEZHNAVETS, Vasily V.; MAYSAK, Natalia N.; HIHINIAK 1, Yury H.; BORODIN, Oleg I.; MIAMIN, Vladislav Ye.; GAIDASHOV, Alexey A.; NIKITIUK, Leonid A. (Zenodo, 2019)
Philodina gregaria Murray, 1910 (Fig. 3B) Philodina gregaria Murray, 1910: 42 – Dartnall & Hollowday 1985: 33, Donner 1965: 202, Kutikova 2005: 221 : Published as part of LUKASHANETS, Dzmitry A., VEZHNAVETS, Vasily V., MAYSAK, Natalia N., HIHINIAK 1, Yury H., BORODIN, Oleg I., MIAMIN, Vladislav Ye., GAIDASHOV, Alexey A. & NIKITIUK, Leonid A., 2019, Rotifers (Rotifera) from the inland waters and terrestrial habitats of East Antarctic oases (Enderby Land and Prydz Bay), pp. 67-86 in Fragmenta Faunistica 62 (2) on page 75, DOI: 10.3161/00159301FF2019.62.2.067, http://zenodo.org/record/6252396 : {"references": ["MURRAY J. 1910. British Antarctic Expedition, 1907 - 9, under the command of Sir E. H. Shackleton, c. v. o. Reports of the Scientific Investigations, London, 1 (Biology, 3): 41 - 73.", "DARTNALL H. J. G. & HOLLOWDAY E. D. 1985. Antarctic rotifers. British Antarctic Survey, Scientific Reports 100: 46.", "DONNER J. 1965. Ordnung Bdelloidea (Rotatoria, Radertiere). Bestimmungsbucher zur Bodenfauna Europas, 6. 1 - 297. Berlin: Akademie.", "KUTIKOVA L. A. 2005. Bdelloid rotifers in the fauna of Russia. Moscow: KMK Scientific Press, 315 pp. [In Russian]"]}